DEVELOPMENT METHODS AND INTEGRATED CONTROL OF SPEED AND POWER QUALITIES OF HIGH CLASS HANDBALL PLAYERS - Dushabaev Dilshodbek Shavkatbekovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the development methodology and complex control of the speed-power qualities of high-class handball players